Nature-Based Solutions as a Tool for Sustainable Urban Drainage: Connections with the UN 2030 Agenda SDGs and Implications for Cities - Santos, Juliana Moura; Nascimento, Ana Paula Branco do (Technical and Scientific Journal Green Cities, 2025)
Objective – To understand how Nature-Based Solutions (NBS) function as tools to promote more sustainable urban drainage, while also analyzing their relationship with the Sustainable Development Goals (SDGs) of the UN 2030 Agenda. Methodology – Systematic Literature Review (SLR), with the selection of 20 articles indexed in the Scopus database. The analysis combined quantitative aspects (distribution of publications, journals, fields) and qualitative aspects (methods, challenges, trends), mapping the connection with the SDGs. Relevance – The study advances by mapping not only the SDGs directly related to the topic, but also indirect connections with sustainable urban drainage, offering a systemic perspective that is still little explored in the national literature. The innovative character of this study lies in the cross-cutting approach between NBS and SDGs, revealing interfaces among environmental, social, and urban policies. Results – The findings highlighted SDGs 6 (Clean Water and Sanitation), 11 (Sustainable Cities), and 13 (Climate Action), which are directly related to sustainable urban drainage. SDGs 3 and 12 showed indirect connections. The articles emphasized multiple benefits of NBS, including flood reduction, water quality improvement, and the enhancement of urban áreas. Theoretical Contributions – Expands the understanding of NBS as a cross-cutting strategy for the SDGs, consolidating a perspective that integrates green-blue infrastructure, governance, climate resilience, and socio-environmental justice, areas that remain underexplored in Brazil. Social and Environmental Contributions – Demonstrates that the application of NBS reduces flood peaks, improves water resources and provides social co-benefits, such as recreational areas and greater community limitations, its connection to SDGs 6, 11 and 13 and other interconnected objectives of the 2030 Agenda while paving the way for measurable indicators that assist managers in public decision-making.